New trends in pediatric antihistamine use (Canadian Dermatology Today, 2022)
In recent years, there has been a move away from the use of traditional first-generation antihistamines (AH) in favour of newer, non-sedating antihistamines. These second and third-generation antihistamines have evolved into mainstays of treatment in the treatment of allergic diseases. They are widely used in dermatology in the management of urticaria as well as for multiple off-label uses including pruritus, insect bite reactions, mastocytosis and other mast-cell releasing diseases. They are faster-acting, safer, and more efficacious than traditional first-generation sedating antihistamines. There is also growing evidence to support the long-term use of newer generation antihistamines as potential disease-modifiers in the pediatric atopic march from infancy through childhood.